Evaluation of an enhanced recovery protocol on patients having radical cystectomy for bladder cancer - Liu, Bonnie; Domes, Trustin; Jana, Kunal (Canadian Urological Association Journal, 2018)
Introduction: Enhanced recovery after surgery (ERAS) protocols are multimodal perioperative care protocols that are designed to shorten recovery time and reduce complication rates.1,2 An ERAS protocol was implemented in the Saskatoon Health region for radical cystectomy patients in 2013. This study evaluates the safety and efficacy of the protocol for patients having radical cystectomy for bladder cancer. Methods: Length of stay (LOS), early in-hospital complication rates, 30-day readmission rates, age, and gender were collected for patients seen for bladder cancer requiring radical cystectomy in Saskatoon between January 2007 and December 2016. Of these patients, 176 were pre-ERAS implementation (control group) and 84 were post-ERAS implementation (experimental group). The data from each variable was compared between the groups using a Z-test. Results: There was no significant difference in age or gender of patients between the groups. Average LOS pre-ERAS was 14.25±14.57 days, which is significantly longer than the post-ERAS average of 10.91±8.56 days (p=0.043). There was no significant difference in 30-day readmission rate (19.87% pre-ERAS vs. 19.05% post-ERAS; p=0.873) or complication rate (51.7% pre-ERAS vs. 46.4% post-ERAS; p=0.425). Conclusions: The implementation of an ERAS protocol for radical cystectomy reduces LOS, with no effect on early complication rates or 30-day readmission rates. This indicates that the protocol is safe for patients when compared to previous practices and is an effective means of reducing LOS.